ダイ 29 ジ ナンキョク チイキ カンソク タイ キショウ ブモン ホウコク 1988 - 松原, 廣司; マツバラ, コウジ; 土井, 元久; ドイ, モトヒサ; 上窪, 哲朗; ウエクボ, テツロウ; 岡田, 憲治; オカダ, ケンジ; Matsubara, Kouji; Doi, Motohisa; Uekubo, Tetsuro; Okada, Kenji (1990)
P(論文) この報告は第29次南極地域観測隊気象部門が, 1988年2月1日から1989年1月31日まで昭和基地において行った地上および高層気象観測の結果並びに1987年11月から12月に行った「しらせ」船上でのオゾン観測結果をまとめたものである。観測方法, 設備, 結果の取り扱い等はほぼ第28次観測隊と同じである。越冬期間中特記される気象現象としては, 次のものがあげられる。1) 8月下旬から9月上旬にかけて, 大規模な成層圏突然昇温と昇温に伴うオゾン全量の急激な増加が観測された。特に8月の昇温の規模は, 観測開始以来の最大であった。2)年間ブリザードの襲来が回数, 日数共に少なく1960年以来の最低を記録した。3) 3月21日に昭和基地の北を通過した低気圧が急激に発達したため, 最大瞬間風速49.9m/sを記録し, 月の最大瞬間風速記録を更新した。4) 6月の月平均気圧(海面)は, 1001.5mbを記録し, 月の第1位の記録を更新した。また, この値は年の第2位の記録を更新した。 This paper describes the results of meteorological observations (mainly surface and upper-air) at Syowa Station from February 1,1988 to January 31,1989 and ozone observations on board the icebreaker SHIRASE during the period from November 1987 to December 1987. Methods and equipment for observations were the same as JARE-28. Surface and upper-air data were sent to World Meteorological Center at Melbourne via Mawson Station according to the WMO regulations. Remarkable chracteristics are as follows : 1) A large-scale stratospheric sudden warming and an abrupt increase of total column ozone took place during the period from the end of August to early September. It was experienced for the first time that such a large sudden warming occurred in August. 2) The frequency of blizzards that hit our station was the minimum since 1960. 3) On March 21,the cyclone passing over the sea north of Syowa Station became strong abruptly and strong wind blew. Maximum instantaneous wind speed was 49.9m/s, which was the maximum record in March. 4) Monthly mean sea level pressure of June was 1001.5mb, which was the maximum record in June and the second highest for the total period of observation. departmental bulletin paper